La valoración de la propiedad, planta y equipo y su evolución en el patrimonio de la empresa - Juca Mantilla, Zaida Elizabeth (2015)
This research work is directly related to the valuation of the plant and situation is unobserved from various points and in various companies limiting their actions and above all make decisions based on reliable accounting events on the economic and financial situation at the end of equipment owned one accounting period. The aim of the study is to determine that the proper valuation of inventories incurred in a dynamic and strategic process to achieve sustainable business growth in stands where the organization assimilates regulatory changes and becomes competitive market opportunities improve profitability by the activities Additionally, the work has the main conclusions that came after structuring the main procedures to assess plant and equipment property in order to publicize the work done and especially to give alternatives to achieve maximum utilization of resources is finally important to note that the work done can be used by different users in order to study because it is a similar situation that can lead to reasonable protection of its resources against external threats Assessment of property plant and equipment is an accounting process that led effectively provides big financial returns for its investors